ATHLETICS DEPARTMENTS AND THEIR CATEGORIZATION - Samekeev Izzet Muratovich (Proximus Journal Publishing, 2024)
Athletics, also known as track and field, encompasses a variety of running, jumping, throwing, and combined events. In Uzbekistan, athletics departments, such as the Uzbekistan Athletics Federation, play a critical role in overseeing national competitions, athlete development, and promoting the sport. Categorized within sports federations, athletics departments work with regional clubs and schools to nurture talent and represent Uzbekistan in international competitions.
Keywords: Athletics; track and field; Uzbekistan Athletics Federation